Socio-economic sustainability approaches applied within the conservation strategies of the historical city of Jeddah “The case study of Al-Balad” - Bamuqabel, T.; Golkarian, Sh. (Amazonia Investiga, 2023)
Sustainability has gained significant attention in recent years due to the critical circumstances of global crises. The historical city of Al-Balad has been the center of attention given to the conservation field aiming to preserve the city's identity while considering its historical role, unique buildings, the past of the city, and its people. Socio-economic sustainability in conserving the old district of Al-Balad is achieved through multiple strategies including the economic opportunities offered for the locals in terms of business development, as well as attracting tourists, increasing property value, and adaptive reuse. The aim of the research is to detail the socio-economic heritage preservation techniques and analyze the efforts made by the Saudi government and civil organizations to create a series of recommendations based on the recent research and literature review to evaluate its effectiveness in protection. The research methodology used is a qualitative approach, with field visits to take a closer look at current activities and progress in the field, as well as peer literature reviews and official sources. The findings of the research show a development in the social and economic aspects of the community as a result of the efforts related to the conservation of the heritage place.